NEW TRENDS IN MULTILINGUALISM AND MINORITY LANGUAGES ON A GLOBAL SCALE - Erzhen V. Khilkhanova (Vestnik Volgogradskogo gosudarstvennogo universiteta. Serija 2. Jazykoznanije, 2020)
The article examines current trends in language policy and attitudes towards multilingualism and minority languages in the European Union, the USA, and Australia. On the example of some languages (Basque, Breton, Corsican, Sámi etc.) various factors affecting the current situation of minority languages are analyzed with priority to the state language policy. Special attention is concentrated on a new phenomenon in European sociolinguistics – the emergence of “new speakers” from minority groups who have learned these languages not in the family, but due to the educational system. Regarding the US language policy, the situation with the languages of North American Indians is described through some positive changes that have occurred in the economic, legal, cultural and linguistic environment of Indian tribes. The Australian case is analyzed as an equally striking example of progress from banning the use of aboriginal languages to modern programmes of their revitalisation. On the basis of the considered cases the author points to the importance of such factors as language activism and the financial and economic situation of minorities themselves. It is concluded that the change in the value paradigm only sets the framework conditions for the implementation of language rights but does not guarantee their success.